Clostridium Difficile Infection in Childhood: Case Series - Parusheva P.; Pekova L.; Angelova S.; Bureva B. (Acta Medica Bulgarica)
Clostridioides (formerly Clostridium) difficile is a spore-forming, anaerobic, toxin- producing gram-positive bacillus. Recently, its frequency as a cause of diarrhea in childhood has been increasing, which necessitates its further in-depth study.